Effective action approach to the Leggett’s mode in two-gap superconductors - Ghimire, Bal Ram; Chimouriya, Shanker P; Gyawali, Basant (BIBECHANA, 2020)
When electrons of two electronic bands participate in superconducting phenomena, it is said to be two gap superconductor. There are two set of cooper pairs in different energy gap with different energy. The observation of Leggett’s mode in two band superconductor provides an additional information about superconductor. By using the effective action, the thermodynamic potential in the case of neutral and charged two gap superconductor are calculated. Using phase dependent action, we investigate a collective excitation (Leggett’s mode) corresponding to small fluctuations of the relative phase of two condensates in two band superconductor. We consider the possibility of observing Leggett’s mode in MgB2 superconductor and conclude that for the known values of two band model parameters for MgB2, Leggett’s mode rises above the two particle threshold. BIBECHANA 17 (2020) 74-79